Study the germination of seeds of Sudanese grass (Sorghum × drummondii) treated by ethylene glycol and propylene glycol cryoprotectants - Madiyeva, A.N.; Silantyeva, M.M. (Fundamental and Experimental Biology, 2023)
The present study was conducted at an objective study of the seeds of Sudanese grass for cryopreservation and viability of seeds. Laboratory studies were carried out on 4 varieties of Sudanese grass: Nika, Tigai, Novosibirskaya 84, and Alina. The results showed that cryopreservation had a positive effect on germination rates. Thus, in the Tugay variety, the best germination rates of 99 % were observed in the variant with cryopreservation with defrosting of seeds in a water bath. A positive effect was also noted for the variety Novosibirskaya 84, where cryopreservation during defrosting of seeds at room temperature increased germination by 7 % and amounted to 89 %. For varieties Nika and Alina, cryopreservation had the opposite effect, the indicators decreased by 27 %, by 10 %, respectively, compared with control. Under conditions of seed defrosting at room temperature, cryopreservation with ethylene glycol and propylene glycol had a positive effect on the germination of seeds for all varieties, with the exception of the Alina variety, where its germination did not differ significantly from the control. Cryopreservation using ethylene glycol under conditions of seed defrosting at room temperature showed that for the Tugay variety the recommended concentration of the cryoprotectant is 5 % and 10 %. The germination rate was 98 %, and the germination energy was 99 % and 96 %, respectively. Ethylene glycol concentration of 20 % significantly reduced the germination rate and amounted to 47 %. For the Nika variety, we recommend using a concentration of 15 %; but the concentration of 10 %, the germination rate is lower and amounts to 58 %. Almost 100 % germination were observed in the Novosibirskaya 84 variety at concentrations of 5 % and 20 %. Thus, the recommended method for thawing Sudan grass seeds after cryopreservation using ethylene glycol and propylene glycol cryoprotectants is thawing at room temperature. These results can be used to create a cryo collection of Sudan grass seeds.